Effects of Comprehensive Discharge Planning From an Intensive Care Unit on Adverse Events and Intensive Care Unit Readmission - กาจารี ปิยวรา; ธงชัย ฉวีวรรณ; สำราญญาติ มยุลี (Nursing Journal CMU, 2019)
Patients who are discharged from an intensive care unit (ICU) are at particular risk for adverse events leading to ICU readmission within 72 hours due to factors such as the severity of their illness and the complexity of their case. This quasi-experimental research was employed by using a two group post-test only design and aimed to examine the effects of comprehensive discharge planning (CDP) from the ICU on adverse events leading to ICU patient readmission within 72 hours. The participants were purposively selected and comprised of 50 critically ill surgical patients who were confined to the general ICU of Lampang Hospital, Thailand from April to October 2014. Subjects were assigned to a control group (n=25) and an experimental group (n=25). The severity of their illness and the characteristics of discharge from the ICU were similarly matched for both groups. The experimental group received a CDP from the ICU based on the comprehensive discharge plan for the ICU developed from the researcher et al., (2013) under the concept of discharge planning of Mckeehan (1981), and from the literature reviewed, which consisted of a discharge plan for the critically ill patients, a critical care outreach service, and care coordinated by the ICU discharge nurse. The control group received the usual discharge care. The research instruments consisted of the comprehensive discharge plan for the ICU and the outcomes record form which included a record of adverse events and ICU readmission within 72 hours, developed by the researcher. The content validity of the research instrument was done by experts. The content validity index [CVI] of the outcomes record form was 1.0. The feasibility and appropriateness of the comprehensive discharge plan for the ICU was able to be utilized in the units. The interrater reliability, which was done between the researcher and an ICU expert nurse, was 1.0. Data analysis were done using chi-square test. The results of this study demonstrated that there were significant differences in adverse events between the experimental group and the control group, which included respiratory problems (p < .001), infections (p < .001) and fluid volume overload (p < .05). There was no significant difference between the two groups for ICU readmission within 72 hours. From the findings, the researcher suggested that further studies of the effects of the DCP from the ICU on the ICU readmission within 72 hours should be done among premature discharge patients from the ICU, in order to obtain enough evidence for a systematic review and to enhance further knowledge on the continuity of care of critically ill patients.